Species With Greater Aerial Maneuverability Have Higher Frequency of Collisions With Aircraft: A Comparative Study - Fernández-Juricic, Esteban; Brand, James; Blackwell, Bradley F.; Seamans, Thomas W.; DeVault, Travis L. (Frontiers in Ecology and Evolution, 2018)
Antipredator responses may appear unsuccessful when animals are exposed to approaching vehicles, often resulting in mortality. Recent studies have addressed whether certain biological traits are associated with variation in collision risk with cars, but not with higher speed-vehicles like aircraft. Our goal was to establish the association between different species traits (i.e., body mass, eye size, brain size, wing loading, wing aspect ratio) and the frequency of bird collisions with aircraft (hereafter, bird strikes) using a comparative approach controlling for the effects of shared ancestry. We proposed directional predictions as to how each of the species traits would affect the frequency of bird strikes. Considering 39 bird species with all traits represented, the model containing wing loading had the best fit to account for the variance in bird strikes across species. In another model with 54 species exploring the fit to different polynomial models but considering only wing loading, we found that wing loading was negatively and linearly associated with the frequency of bird strikes. Counterintuitively, species with lower wing loading (hence, higher maneuverability) had a higher frequency of bird strikes. We discuss potential non-mutually exclusive explanations (e.g., high wing loading species fly faster, thus gaining some extra time to avoid the aircraft flight path; high wing loading species are hazed more intensively at airports, which could lower collisions, etc.). Ultimately, our findings uncovered that species with low wing loading get struck at a higher rate at airports, which reduces the safety risk for humans because these species tend not to cause damaging strikes, but the consequences of their potentially higher local mortality are unknown.